Expected service dimensions and service levels for paratransit considering future mobility needs in emerging countries. (August 2022) - Pandit, Debapratim; Sharma, Deepa
Highlights: Mobility-as-a-Service (MaaS) promises improved modal efficiency and integration among public transit and flexible paratransit services (FPS). Key service dimensions and issues of flexible paratransit services are analysed in the context of MaaS. Expected service level for these service dimensions are determined using the level of service (LOS) approach based on user perception. Ride matching as per expected waiting time and service hours via MaaS agencies would ensure proper demand-supply match and fleet size determination. Abstract: In emerging countries, flexible transport systems (FTS) are mostly informal and are provided by individual paratransit operators/drivers. These services are largely unregulated thus resulting in uncoordinated operations with poor service quality. Earnings and working conditions of paratransit drivers/operators are also poor due to loosely regulated fleet size and other operational and regulatory issues which results in further deterioration of service quality. This research identifies key service dimensions and issues of paratransit services and also determines the expected service level for these service dimensions using the level of service approach based on user perception. LOS scales are designed for different service attributes using a five-point satisfaction and importance rating system. For quantitative attributes, five-level LOS scales are determined by applying the Law of Successive Interval Scaling, whereas for qualitative attributes, the same has been developed using the frequency of response for each level of importance for each sub-attribute. Subsequently, we explore various policies and regulatory measures towards reform and redesign of paratransit services and other mobility needs. Operator profitability can be achieved both through the controlled entry of operators through the issue of permits and/or by relaxing the current service level of some service aspects which are at LOS B level of service. The LOS scales can help in future service design of paratransit services in emerging countries which can offer an affordable alternative to ridesourcing and ride-sharing using cars. The study is conducted in two medium-sized cities in India namely Rajkot and Vishakapatnam.